2022
DOI: 10.1111/jocn.16312
|View full text |Cite
|
Sign up to set email alerts
|

National registry‐based data of adverse events in Finnish long‐term professional homecare in 2009–2019

Abstract: Aims and objectives:The aim of this study was to discover the nature of the adverse events in Finnish long-term professional homecare reported by professionals, and to identify the circumstances in which adverse events occur and their consequences.Background: Adverse events are incidents causing unintended and unnecessary harm to older people at home. Safety is a basic human right and a fundamental prerequisite for independent living among older people at home. Few studies have focused on both long-term profes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
(37 reference statements)
0
0
0
Order By: Relevance
“…Practical nurses or care workers made most of the reports. This result is congruent with a previous study conducted in the home care context where data were based on the patient safety incident reporting system called HaiPro (Kivimäki et al, 2022). HaiPro and SPro were both developed by an IT company named Awanic (Ltd), and thus have similar structures (Awanic, 2022).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Practical nurses or care workers made most of the reports. This result is congruent with a previous study conducted in the home care context where data were based on the patient safety incident reporting system called HaiPro (Kivimäki et al, 2022). HaiPro and SPro were both developed by an IT company named Awanic (Ltd), and thus have similar structures (Awanic, 2022).…”
Section: Discussionsupporting
confidence: 89%
“…All reports in the SPro and HaiProsystems are classified as actual or near-miss events, which, in this study, are called observed risks or threats thereof. The proportion of observed risks was greater in this study than that in studies based on the HaiPro-system (Kivimäki et al, 2022). Most of the events occurred in the morning and during the day, whereas in a previous study most patient safety incidents in specialised care settings occurred at night (Kinnunen-Luovi et al, 2014).…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation